Cyclability enhancement of CeO2/Sb2O3 composite electrode via ternary Na-storage reactions. Issue 23 (1st December 2022) - Usui, Hiroyuki; Domi, Yasuhiro; Uehara, Isaki; Itoda, Yoshitatsu; Iwama, Eiji; Oishi, Naoto; Nitta, Noriko; Sakaguchi, Hiroki
Abstract: As a Na-ion battery anode material, we newly designed CeO2 /Sb2 O3 composites ternary Na-storage mechanisms: insertion, conversion, and alloying reactions. The structural analyses confirmed that the CeO2 particles were incorporated well into the Sb2 O3 matrix, on a microscopic scale, in the composites obtained via mechanical milling. The Sb2 O3 electrode showed a high initial reversible capacity of 610 mA h g −1 because of the conversion reaction of Sb2 O3 and its subsequent alloying reaction of Sb, whereas it very poor cyclability owing to large volume changes during these reactions. Furthermore, we newly confirmed reversible Na-insertion reaction of an CeO2 electrode and its excellent cyclability. It was revealed for the first time that reversible Na-insertion and Na-extraction reactions occur, accompanied by lattice expansion and contraction. For the CeO2 /Sb2 O3 composite electrodes, the rapid capacity decay behavior was significantly improved. This indicates that CeO2 contributes to stress relaxation and Na-ion conduction through the insertion reaction. An increase in the Sb2 O3 content in the composite improved the anode performance. The CeO2 /Sb2 O3 (10/90 wt%) composite electrode exhibited excellent anode performance with a capacity of 400 mA h g −1  at the 120th cycle despite its low CeO2 content. Notably, the cyclability could be effectively enhanced using a small amount of CeO2 . Graphical abstract: Image 1